Evaluation des instituts universitaires de technologie et de leurs départements : retour sur 15 années d’expérience - Michel Le Nir (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In the early 2000s, the French Ministry of Education decided to generalize the evaluation to all of the university institutes of technology (UIT). The preferred plan is the result of a co-construction between its departments and the main actors of the UITs national network. The UITs national advisory committee - an authority that associates academics and representatives of the economic world which is already in charge of the programs’ follow-up and renovation – has been entrusted with the management of the new plan. In March 2014 and after those conducted between 2001 and 2013, the Ministry decided to undertaken the fourth campaign of evaluation. If the initiative knew some adjustments according to the waves of evaluation, it had not been the object of a thorough examination to this day. The ambitions initially showed as well as the sizing of the plan, the number of participants mobilized, both on the side of the evaluators and on the side of the evaluated, but also the questions generally aroused by the implementation of evaluative initiatives justify that we return on an experience used for more than fifteen years.